Kajian Biaya Operasional Kapal di Wilayah Indonesia Timur - Yolla Ayutia; Oky Yunna Irawan; Yosi Pahala (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
This study aims to analyze the influence of operating costs, freight costs and tonnage of ships in the distribution of fuel in eastern Indonesia. The data was obtained through interviews and data collection in the field. The problem was solved using quantitative descriptive methods. From this research, it can be concluded that 1) The effect of Ship Operational Costs (OPEX) on Tonnage ships (GT) with the increase in ship Tonnage will increase ship operating costs, or vice versa. 2) The effect of transport costs (Freight Cost) on Tonnage ships (GT) with increasing vessel Tonnage will increase the cost of transporting ships, but the transport costs per liter will be smaller if the size of the ship is getting bigger. 3) The effect of operational costs (opex) on freight costs (Freight Cost) with increasing operational costs (opex) will increase ship freight costs. The ship's operational costs are greatly updated by the component of Depreciation costs, maintenance / repairs and Crew salary. There are many factors and dimensions that affect operational costs and transport costs in eastern Indonesia, therefore, in-depth research needs to be done in the future by including the vessel operating factor and ship load factor, regulation and best practices in other shipping industries.